A New Direction in Teaching Reading Skills Using the PAIKEM Model (Active, Innovative, Creative, Effective, and Enjoyable Learning) for Elementary School Students - Isnaini, Yunisa; Yuniar; Bambang Prasetyo (The Future of Education Journal, 2025)
This study aims to determine the effectiveness of the PAIKEM model (Active, Innovative, Creative, Effective, and Enjoyable Learning) in improving reading comprehension skills (maharah qirā'ah) among fifth-grade students at Madrasah Ibtidaiyah Azharyah Palembang. The research employs a mixed-method approach, combining both quantitative and qualitative methods. The quantitative design uses a pretest-posttest with two groups: the experimental group using the PAIKEM model and the control group using conventional methods. A total of 20 students were selected through purposive sampling. Quantitative analysis shows a significant improvement in maharah qirā'ah skills after the application of the PAIKEM model, with the t-test results indicating a significance value of 0.001 (p < 0.05). Qualitative analysis, based on interviews and observations, indicates that students were more engaged and motivated in learning after the implementation of the PAIKEM model, as the learning process became more interesting, active, and enjoyable. The findings of this study conclude that the PAIKEM model is effective in improving maharah qirā'ah skills among fifth-grade students at Madrasah Ibtidaiyah Azharyah Palembang.